Case Report: Histological Evaluation of Deep Tissue Remodeling After Extended Mode of Fractional RF Microneedling - MD, Chien-Ming Chen; MD, Jieyang Jhuang (Archives of Clinical and Medical Case Reports, 2025)
Fractional radiofrequency (RF) microneedling is commonly used for skin and body rejuvenation by inducing controlled thermal micro-injuries that stimulate collagen and elastin production. However, conventional techniques often cause discomfort, especially when targeting deeper tissues. This case report evaluates the histological effects of the Exion Fractional RF device using its Extended Mode, which creates a thermal gradient reaching deeper layers without full needle penetration. A 40-yearold male subject (BMI 22.9) received a single-pass treatment to the face and abdomen, with insulated microneedles delivering monopolar RF energy at varying depths (1.0–4.0 mm) and intensities (60% and 100%). Biopsies were taken immediately post-treatment, and on Days 7 and 30. Histological analysis using H&E and Masson's trichrome staining revealed a consistent 4-mm thermal gradient in abdominal tissue, with evidence of collagen coagulation and remodeling extending beyond needle depth, while preserving the integrity of the epidermis. By Day 30, early neocollagenesis and signs of adipocyte apoptosis, including membrane disruption and fibrotic changes, were noted. These findings suggest that the Extended Mode enables effective deep tissue remodeling and adipose targeting while minimizing epidermal disruption.